An Evaluation Implementation of the Head National Library Regulation No. 11/2017 at SMP N 5 Batusangkar - Dina Ratna Sari; Adripen Adripen; Muhammad Husni Shidqi; Jamilus Jamilus; Dona Afriyani (CV. Creative Tugu Pena, 2025)
To improve library management in accordance with the National Library Standards (SNP), schools must comprehensively implement the Head of Library Regulation No. 11 of 2017. This study aims to examine the implementation of: (1) collection standards, (2) facilities and infrastructure standards, (3) service standards, and (4) library personnel standards at SMP N 5 Batusangkar based on the Head of Library Regulation No. 11 of 2017. This research employed a qualitative evaluation using the discrepancy model. The study was conducted at SMP N 5 Batusangkar, involving three key informants: the school principal, the head librarian, and a library staff. Research instruments consisted of interview guidelines, observation sheets, and documentation. Data were collected through in-depth interviews, participant observation, and document analysis. Data analysis was carried out using data triangulation, including source and technique triangulation. The results of the study show that: from the 12 library collection standards, only 1 standard has not been implemented. Second, from the 5 standards of library facilities and infrastructure, the 4 standards have not been implemented properly. Third, from the 10 library service standards, only 4 standards have been implemented, but the other 6 standards have not been implemented properly. Fourth, from the 6 standards of library staff, only 4 standards have been implemented, but the other 2 standards have not been implemented properly. In other words, the library of SMP N 5 Batusangkar has implemented the Head of Library Regulation No. 11 of 2017, but still needs improvement in several aspects.